2015
DOI: 10.1007/s10545-015-9845-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective 10‐year study of individualized, intensified enzyme replacement therapy in advanced Fabry disease

Abstract: Weekly enzyme infusions slow the decline of renal function in a subgroup of more severe patients thus showing that existing ERT can be further optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
1
36
0
1
Order By: Relevance
“…A recent study by Germain and colleagues showed that less affected individuals with a better preserved kidney function at baseline benefited from ERT, experiencing better renal and cardiovascular outcomes during the observational period [36]. Moreover, in male FD patients, enhanced therapeutic outcomes may occur if we increase the ERT dose [35, 37, 38], or frequency of infusions [39], in combination with intensified additional medication such as ARBs and ACE inhibitors [16]. In patients with amenable mutations, pharmacological chaperones have been shown as a useful therapeutic alternative [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Germain and colleagues showed that less affected individuals with a better preserved kidney function at baseline benefited from ERT, experiencing better renal and cardiovascular outcomes during the observational period [36]. Moreover, in male FD patients, enhanced therapeutic outcomes may occur if we increase the ERT dose [35, 37, 38], or frequency of infusions [39], in combination with intensified additional medication such as ARBs and ACE inhibitors [16]. In patients with amenable mutations, pharmacological chaperones have been shown as a useful therapeutic alternative [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterised by intra-lysosomal accumulation of globotriaosylceramide (Gb3) and other related glycolipids sub-types (e.g., glycosphingolipids) in many cell types, including blood vessels throughout the body. This buildup initiates a cascade of events, starting with the disruption of basic metabolic processes at the cellular level and progressing to inflammatory events and cell death, thereby affecting the system as a whole with an increase of renal, cardiac, cerebrovascular, and skin complications [1,2]. …”
Section: Introductionmentioning
confidence: 99%
“…FD management and therapy employs the regular use of agalsidase-alpha (Replagal) and agalsidase-beta (Fabrazyme). They are reported as improvers of renal and cardiac function, and cerebrovascular flow [1,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Cornea verticillata is the most distinctive clinical ocular finding of Fabry disease (Sher et al 1979;Sodi et al 2006). Enzyme replacement therapy (ERT) has been used for treatment of Fabry disease for over 10 years, and some recent studies have reported the long-term therapeutic efficacy of ERT on cardiac or kidney function over 10 years (Germain et al 2015;Schiffmann et al 2015). While little is known about corneal changes associated with long-term ERT (Fledelius et al 2015), we report a case of marked regression of corneal deposits in a patient with Fabry disease 16 years after ERT.…”
Section: Referencesmentioning
confidence: 91%